Diversification of income from family farming during 2018 in Tehuatzingo, Libres, Puebla - Arteaga Domínguez, Margarita; Sánchez Morales, Primo; Romero Arenas, Omar; Ocampo Fletes, Ignacio; Rivera Tapia, Antonio; García Pérez, Israel Gerardo (Revista Mexicana de Ciencias Agrícolas, 2021)
Multiactivity is a current phenomenon in rural households. The objective of this work was to analyze the sources of income of peasant families in a subsistence family farming (AF) context due to the importance of meeting food needs first at home. The primary information was obtained by survey (N= 90 and n= 46) through simple random sampling with agricultural producers of maize and pumpkin in the ejido Tehuatzingo, Libres, Puebla. Two management systems were studied: the monoculture system (SMo) and the modified milpa system (SMM). More than 50% of the workforce in the two groups (58% in the SMM and 61% for the SMo) is related to family work. The activity of producers is considered multi-active (more than half of their income is derived from non-agricultural activities), such is the case of SMo producers. The opposite happens with SMM where it is estimated that 46% of its income derives from activities outside the agricultural plot, therefore, it is considered as specialized AF (more than half of its income comes from agricultural activities). It is concluded that the group with the greatest tendency to diversify sources of income is the SMM, as reflected in the Simpson Index where agricultural income is highest as a result of crop diversification and sale. This contrasts with the SMo which obtains higher economic remuneration outside the agricultural plot.